Classical description of charge exchange involving He-like or Li-like ions in Rydberg states in plasmas. (21st January 2016) - Kryukov, N; Oks, E
Abstract: A purely classical description of energy terms of one-electron Rydberg quasimolecules (hereafter, RQ1) consisting of one electron and two fully stripped ions of charges Z and Z ′, where Z ′ ≠ Z, had been previously published by one of us. The analysis of the crossings of the energy terms led to a classical description of charge exchange either between a hydrogen-like ion of the nuclear charge Z with a fully stripped ion of the charge Z ′ or between a hydrogen-like ion of the nuclear charge Z ′ with a fully stripped ion of the charge Z . Later applications included, e.g., the influence of electric and magnetic fields, as well as of the screening by plasma electrons. In the present paper we extend the classical description of energy terms to two-electron Rydberg quasimolecules (RQ2), consisting of two electrons and two fully stripped ions of charges Z and Z ′, and to three-electron Rydberg quasimolecules (RQ3), consisting of three electrons and two fully stripped ions of charges Z and Z ′. We show that classical energy terms of RQ2 and RQ3 also exhibit crossings like the energy terms of RQ1. The crossing of terms of RQ2 occurs at a larger internuclear distance compared to the crossing of the corresponding terms of RQ1, so that the cross-section of the charge exchange for RQ2 is larger than the corresponding cross-section for RQ1. The crossing of terms of RQ3 occurs at an even larger internuclear distance compared to the crossing of the corresponding terms of RQ2, so that the cross-section of the charge exchange for RQ3 is even larger than the corresponding cross-section for RQ2. Thus, the classical roots of charge exchange are revealed not only by the example of RQ1 systems, but also by the examples of RQ2 and RQ3 systems. Our results contribute to advance the understanding of the quantum-classical correspondence and can be used in applications where charge exchange plays the key role.